Psychological influence of conformism on the formation of students’ value orientations in adaptation to social environment - Toxanbayeva, Nurgul; Salimova, Gulnar; Mandykayeva, Almagul; Spatay, Aygul; Aitysheva, Aigul (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the psychological impact of conformism on the formation of students’ value orientations in the process of social adaptation. An original interpretation of conformism is proposed as a mechanism of value contagiousness, within which norms and attitudes spread in the student environment, similar to cultural viruses. Through rituals, repetition, and group pressure, individual meanings are transformed, often without a conscious choice of the individual. On the basis of the developed V-ConScale scale, a model for quantitative diagnostics of a student’s susceptibility to value infection and the level of their reflexive stability is presented. This work combines philosophical and psychological analysis with an applied pedagogical focus and offers tools for monitoring, preventing, and supporting the processes of students’ semantic adaptation in the university environment. The concept can be useful for designing educational strategies aimed at developing an authentic, critically thinking subject.